2011
DOI: 10.1159/000329347
|View full text |Cite
|
Sign up to set email alerts
|

Combining Movement Kinematics, Efficiency Functions, and Brinley Plots to Study Age-Related Slowing of Sensorimotor Processes: Insights from Fitts’ Task

Abstract: Background: Measurement of changes in human information-processing capacities underlying slowing of sensorimotor processes is an important challenge for aging research. Methods exist to estimate the magnitude of slowing and variability coefficients, but attempts to apply them in motor tasks have been scarce. In the present experiment we combined movement kinematic analysis, efficiency functions and Brinley plot to assess age-related slowing and variability of sensorimotor processes in a discrete Fitts’ aiming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 68 publications
4
25
1
Order By: Relevance
“…However, the absence of end-point differences in goaldirected aiming movements to visual target (e.g. Welsh et al 2007;Rey-Robert et al 2012) suggested that the presumed alteration of inverse internal models could be compensated for through online adjustments of the trajectory. However, due to the visual knowledge of the result, these adjustments could have also been the consequence of a learning effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the absence of end-point differences in goaldirected aiming movements to visual target (e.g. Welsh et al 2007;Rey-Robert et al 2012) suggested that the presumed alteration of inverse internal models could be compensated for through online adjustments of the trajectory. However, due to the visual knowledge of the result, these adjustments could have also been the consequence of a learning effect.…”
Section: Resultsmentioning
confidence: 99%
“…Two main methods have been used to determine these phases. The first one divides movements into acceleration and deceleration phases, with the instant of peak velocity being the division point Darling et al 1989;Goggin and Meeuwsen 1992;Goggin and Stelmach 1990;Lyons et al 1996;Murrell and Entwisle 1960;Rey-Robert et al 2012;Welford et al 1969;Yan et al 2000). Results of these studies showed age-related differences in the duration of the acceleration and/or deceleration phases, as well as in the positional, velocity and acceleration profiles.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies showed that movement durations lengthened more in older than in young participants as ID increased (Haaland, Harrington, & Grice, 1993;Ketcham et al, 2002;Rey-Robert et al, 2012;Teeken et al, 1996;Temprado et al, 2013;Welford, Norris, & Shock, 1969;York & Biederman, 1990). As a consequence, the slope of Fitts' law is generally smaller in young than in older adults (Rey-Robert et al, 2012;Sleimen-Malkoun et al, 2013;Temprado et al, 2013). Previous studies found that, compared to increasing movement accuracy (W manipulation), increasing movement amplitude (D manipulation) results in a steeper ID-MT slope (Sleimen-Malkoun, Temprado, Huys, Jirsa, & Berton, 2012;Temprado et al, 2013).…”
Section: Previous Findings In the Fitts' Taskmentioning
confidence: 99%
“…Declines of cognitive (e.g., Salthouse, 1996; Bashore et al, 1997) and motor (e.g., Rey-Robert et al, 2012; Temprado et al, 2013) performance are widely used in the literature to assess the effects of aging in the neuro-behavioral system. However, qualitative changes (i.e., the strategies used to adapt to task constraints) may also provide functionally meaningful information about age-related alterations of brain and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Since EFs and processing speed are seriously affected in cognitively impaired patients (CIP), one can expect at least an amplification of these variations generally observed in HOA. Indeed, it has been suggested that EFs are strongly involved in Fitts’ task, especially during the deceleration phase of the movement (see Rey-Robert et al, 2012; Sleimen-Malkoun et al, 2013; Temprado et al, 2013). …”
Section: Introductionmentioning
confidence: 99%